Experimental investigation of mechanical and fracture properties of offshore wind monopile weldments: SLIC interlaboratory test results - Mahmanparast, Ali; Taylor, Jessica; Brennan, Feargal Peter; Tavares, I. (Wiley, 2018)
S355 structural steel is commonly used in fabrication of offshore structures including offshore wind turbine monopiles. Knowledge of mechanical and fracture properties in S355 weldments and the level of scatter in these properties is extremely important for ensuring the integrity of such structures through engineering critical assessment. An interlaboratory test programme was created to characterise the mechanical and fracture properties of S355 weldments, including the base metal, heat‐affected zone, and the weld metal, extensively. Charpy impact tests, chemical composition analysis, hardness tests, tensile tests, and fracture toughness tests have been performed on specimens extracted from each of the 3 material microstructures. The experimental test results from this project are presented in this paper, and their importance in structural integrity assessment of offshore wind turbine monopiles has been discussed. The results have shown a decreasing trend in the Charpy impact energy and Jmax values with an increase in yield stress from base metal to heat‐affected zone to weld metal. Moreover, the JIC fracture toughness value in the heat‐affected zone and weld metal is on average around 60% above and 40% below the base metal value, respectively. In addition, the average Charpy impact energy value in the heat‐affected zone and weld metal is around 5% and 30% below the base metal value, respectively. The effects of mechanical and fracture properties on the critical crack size estimates have been investigated, and the results are discussed concerning the impact of material properties on structural design and integrity assessment of monopiles.
Keywords: Fracture toughness; Monopile; Offshore wind; S355 steel; Weldments